Qirāʾāt Shādhdhah in Legal Verses: A Study of Usury in the Interpretation of Abū Ḥayyān - Widayati, Romlah (IAIN Ponorogo, 2024)
This study aims to highlight the impact of qirāʾah on Islamic law. This study also explains Ibn Ḥayyān's interpretation in interpreting the verse on usury so that it has an impact on Islamic law. This research is descriptive-analytic research using a literature study. This study describes the interpretation put forward by Abū Ḥayyān, which is then analysed by using qirāʾāt shādhdzah in interpreting legal verses, which is devoted to the verse that discusses usury. The findings of this study indicate that Abū Ḥayyān's interpretation of QS. al-Baqarah: 279-280 emphasises the compatibility between one verse and another, by understanding the causes of the revelation of the verse, and referring to the principle of al-ʿibrah bi-ʿumūm al-lafẓi lā bi-khuṣūṣ as-sabab. Differences in qirāʾah enrich the understanding of the verse linguistically. This study concludes that qirāʾāt shādhdhah can be used to support or strengthen legal understanding, thus adding depth to linguistic legal interpretation.